The Influence of the Use of Mobile Media Facilities in Online Learning During the Covid-19 Pandemic on the Learning Outcomes of Social Studies Subjects at UPT SMP N 2 Koto Salak - Caterina Lo (Budapest International Research and Critics University, 2022)
This research is motivated by the use of mobile media facilities in the online learning process which is still not optimal. Based on the phenomenon found by researchers in the field, internet network access which is still difficult to reach makes students less understanding of the material given by the teacher. The purpose of this study was to determine the effect of using mobile phone media facilities in online learning during the covid-19 pandemic on student learning outcomes for social studies subjects at UPT SMP N 2 Koto Salak. This type of research is quantitative. The population of this research is the students of SMP N 2 Koto Salak with as many as 43 students taken with the slovin formula. The data was processed using simple linear regression using a questionnaire. The results showed that the implementation of online learning was considered sufficient with a TCR value for learning outcomes of 71.91%, mobile media facilities were considered sufficient with a TCR value of 75.38%, the use of mobile media facilities (X1) had a positive and significant effect on learning outcomes (Y) students at UPT SMP N 2 Koto Salak with a regression coefficient value of 0.334 with tcount 2.082 > t table 2.019 and a value (sig 0.044 <0.05).